Candidiasis Oral Pseudomembran pada Pasien dengan Riwayat Konsumsi Alkohol dan Merokok: A Case Report - Sanggrilla Mahadewi Putri Pratiwi; Sartari Entin Yuletnawati (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Oral candidiasis pseudomembranous is an infection of the oral cavity caused by microorganisms such as fungi, specifically due to the overgrowth of Candida albicans. It frequently manifests in individuals with impaired local or systemic immunity, or those with specific behavioral risk factors. Predisposing factors, such as habitual alcohol consumption and smoking, play a significant role in reducing the resilience of the oral mucosa and altering the balance of the normal oral flora. This case report aims to examine the correlation between behavioral risk factors and the development of pseudomembranous oral candidiasis. A 22-year-old male was reported to have a lesion consisting of thick, raised, whitish plaques that were non-scrapable and asymptomatic. The patient had an unhealthy lifestyle, including alcohol consumption and smoking two packs per day, along with poor oral hygiene. To confirm the suspicion of oral thrush, a potassium hydroxide (KOH) examination was performed, which revealed the presence of Candida albicans. This led to therapeutic management using Nystatin (Candistatin) and Chlorhexidine, complemented by mechanical treatment with a tongue scraper. Pseudomembranous oral candidiasis in this 22-year-old male patient is a classic example in which local behavioral risk factors and lifestyle act as the main triggers of infection.